IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL USED BY EDUCATIONAL GAMES TO IMPROVE STUDENTS' LEARNING OUTCOMES IN INDONESIAN LANGUAGE SUBJECTS CLASS 2 SD INPRES PALUPI - Sitti Adhaniar; Arif Firmansyah; Renawati (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to improve student learning outcomes in Indonesian language subjects through the application of the Problem-Based Learning (PBL) model assisted by educational games in grade 2 of SD Inpres Palupi. The background of this study was motivated by the low learning outcomes of students caused by the lack of student involvement in learning and the lack of use of interesting and interactive learning media. The PBL model, which emphasizes real problem-based learning, is combined with educational games as a learning medium that can increase student motivation and active participation. This study uses the Classroom Action Research (CAR) method consisting of two cycles, with each cycle including the planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation of student activities, and interviews with teachers. The results showed a significant increase in student learning outcomes after the application of the PBL model assisted by educational games. In cycle I, student learning outcomes increased from 60% in the pre-cycle to 66%, and in cycle II, student completion increased to 97%. This increase was also followed by an increase in student active participation in the learning process, which was reflected in their enthusiasm and involvement in class discussions and activities carried out. In conclusion, the implementation of the PBL model assisted by educational games is effective in improving student learning outcomes in the Indonesian language subject in grade 2 of SD Inpres Palupi. The implication of this study is the importance of teachers to integrate problem-based learning models and utilize educational games to improve the quality of learning that is interesting and relevant for students.